Methodology for Enhancing Professional and Technological Competencies of Pre-Service Technology Teachers through Bio-Inspired Modeling - Kenjayev Sherzod Mammatjumayevich (International Journal on Integrated Education, 2026)
This article scientifically substantiates a methodological system for developing professional and technological competencies of future technology teachers based on bio-inspired modeling. The study analyzes the pedagogical potential of bio-inspired modeling in combination with modern forms of organizing technological education, the competency-based approach, STEAM integration, project-based learning, problem-based learning, analogy methods, and design thinking. In addition, methodological mechanisms for the formation of professional and technological competencies under the conditions of the higher education modular-credit system and the 4+2 model were developed. As a result of the study, an algorithm for organizing educational activities based on bio-inspired modeling was proposed, and its impact on the development of students’ technological thinking, design and construction activities, innovative thinking, and engineering competencies was highlighted.